The Effect of Leadership and Organizational Culture on Employee Performance: The Mediating Role of Service Quality (A Study at Sidotopo Public Health Center) - Dian Rakhmaniasari Yusuf; Edi Suhardono; Sulistiyanto Sulistiyanto (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study examines the effect of leadership and organizational culture on employee performance at Sidotopo Public Health Center in Surabaya, with service quality as a mediating variable. A quantitative approach was employed using a saturated sampling technique, involving all 44 employees of Sidotopo Public Health Center as respondents. Data were collected through a five-point Likert scale questionnaire and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS version 4. The results indicate that leadership and organizational culture have positive and significant effects on service quality. Both leadership and organizational culture also positively and significantly influence employee performance. In addition, service quality has a positive and significant effect on employee performance. The mediation analysis confirms that service quality partially mediates the relationship between leadership and employee performance, as well as between organizational culture and employee performance. These findings provide both theoretical and practical implications for public health service organizations, emphasizing the importance of effective leadership, a strong organizational culture, and continuous improvement in service quality to enhance employee performance.